Effects of water washing and torrefaction on the pyrolysis behavior and kinetics of rice husk through TGA and Py-GC/MS. (January 2016) - Zhang, Shuping; Dong, Qing; Zhang, Li; Xiong, Yuanquan
Highlights: Effects of water washing and torrefaction pretreatment were investigated. The activation energy of water washed rice husk was lower than original rice husk. Water washing and torrefaction significantly increased the content of levoglucosan. Abstract: The effects of water washing and torrefaction on the pyrolysis behavior and kinetics of rice husk were investigated through TGA and Py-GC/MS in this study. Two iso-conversional methods, i.e. Starink and FWO methods were applied for determination of the activation energy of original and pretreated rice husk samples at three different heating rates. It was found that activation energy of water washed rice husk was lower than that of original rice husk. Whereas, the activation energy increased with the increase of torrefaction temperature. The result of Py-GC/MS analysis indicated that both water washing and torrefaction pretreatments decreased the contents of acids, ketones, aldehydes and furans, while significantly increased the contents of sugars, especially levoglucosan. The relative content of released levoglucosan from pyrolysis of rice husk sample with combined water washing and 280 °C torrefaction pretreatment is almost 9 times of that from original rice husk, which is about 3%.